The Determinants of International Certification among Manufacturing Firms in Pakistan - Farrukh Iqbal; Aadil Nakhoda (The Lahore Journal of Business)
This study investigates the factors that influence international certification among Pakistani manufacturing firms. About a third of such firms in Pakistan hold one or more certificates related to management or technical processes. The existing literature suggests that this demand is influenced by factors such as sector of activity, market competition, human capital and information environment, ownership type, and available resources. By analyzing a large, random sample of Pakistani manufacturing firms, we find strong correlations between these factors and international certification. We also discover that owner attitude, an aspect overlooked in previous studies, plays a role in the certification decision. While our statistical model does not fully explain the determinants of certification for small firms, we do find that certification is associated with increased profitability among small enterprises. This implies that small enterprise development agencies can improve the effectiveness of their programs by considering certification status as an additional criterion for allocating support funds. The results of our study have policy implications related to exporting, staff training, diffusion of firm ownership, and enhanced information access facilitated by modern technology tools.